2001
DOI: 10.1046/j.1523-1755.2001.060002672.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited urinary concentration and damaged tubules in rats with a syngeneic kidney graft

Abstract: Rats with kidney isografts have a limited capacity to concentrate urine and, at the same time, fail to increase rBSC1 and AQP2 transcripts. This suggests that there is a prolonged damage of renal tubules by ischemia or denervation of the donor kidney, both of which are inevitable in the transplantation procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 27 publications
5
32
0
Order By: Relevance
“…This however, is highly unlikely, because expression, activity, and regulation of transporters was selectively unaffected, reduced, or augmented. In another syngeneic rat kidney transplantation model without rejection, limited urinary concentrating ability and tubular damage was also reported (14). Ischemia after transplantation could be considered as a cause of delayed graft function (19,38), but ischemia/ reperfusion results in a different pattern of changes in expression levels of renal transporters and receptors compared with the present findings.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This however, is highly unlikely, because expression, activity, and regulation of transporters was selectively unaffected, reduced, or augmented. In another syngeneic rat kidney transplantation model without rejection, limited urinary concentrating ability and tubular damage was also reported (14). Ischemia after transplantation could be considered as a cause of delayed graft function (19,38), but ischemia/ reperfusion results in a different pattern of changes in expression levels of renal transporters and receptors compared with the present findings.…”
Section: Discussionsupporting
confidence: 69%
“…Non-immunologic factors are increasingly regarded as important for the prognosis of the transplant. In humans, investigations of changes on the tubular level are hardly possible, and only a few functional studies in animals are available (12)(13)(14)(15)(16)(17)(18)(19)(20). No direct data exist on expression and function of transporters and receptors involved in transport after renal transplantation.…”
mentioning
confidence: 99%
“…Dehydration, which promotes AVP secretion, produces the maximal urinary concentration by enhancing the expression of both AQP2 and rat BSC1 (rBSC1) [10, 15, 16, 17]. We have demonstrated that dehydration markedly increases AQP2 mRNA expression [18], consistent with a dehydration-induced increase in protein synthesis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an examination of the expression of AQP2 in the dehydrated condition, which induces a small but significant urinary concentrating ability even in CRF rat [7], may reveal some of the mechanisms underlying the residual urinary concentrating ability in CRF. The present study is designed to investigate AQP2 expression in a rat model for CRF, in which regulation of rBSC1 expression in response to a reduction of nephron number [17]and to dehydration [16]is almost completely impaired [7]. …”
Section: Introductionmentioning
confidence: 99%
“…27) The molecular cloning of BSC1 14) has enabled us to investigate the expression of this transporter. 5) We ex amined BSC1 expression in a normal rat kidney that achieved maximal urinary concentration in the de hydrated condition, 5) a kidney isograft (a rat with kidney transplantation), 7) and a remnant kidney after 5/6 nephrectomy (a rat model for chronic renal failure), 8) the latter two of which lost the ability to perform maximal urinary concentration even in the dehydrated condition. A marked increase in BSC1 ex pression was observed in the normal kidney from the dehydrated rat 5) and not the kidney isograft 7) or the remnant kidney 8) (Fig.…”
Section: Regulation Of Sodium Transport and Bsc1 Expres Sion In Talmentioning
confidence: 99%